Farmer differentiation and cultivated use system resilience from a perceptive behavioral perspective: influencing mechanisms and governance strategies - Wang, Xin; Wang, Ya Nan (Frontiers in Sustainable Food Systems, 2024)
The adaptive management strategy of the cultivated land use system is crucial for achieving sustainable development, particularly when viewed from the perspective of perceptual behavior. This study integrated farmers' behavior, perceptions, and willingness into the resilience evaluation index system of the cultivated land use system. It also explored the effect of farmer differentiation on the resilience of cultivated land use systems under the influence of socioeconomic systems, thereby providing a scientific reference for the adaptive management of cultivated land use systems. The key findings are as follows: First, in general, the production resilience of the peasant household cultivated land use system was low, with significant resilience differentiation of resource elements and stratification of ecological and scale structures. However, the total resilience remained relatively stable. Second, farmers' cultivated land use systems exhibit uneven resilience, with a lack of production and ecological protection, indicating low efficiency and weak functioning of the cultivated land use system. Third, farmers' differentiation into non-agricultural employment is high, with low dependence on land. The resilience of the cultivated land use system varies significantly among different types of farmers, with imbalance and production deficiency being the main types of resilience in the farmland use system. Fourth, the economic differentiation of farmers and the differentiation of cultivated land use negatively affected the resilience of the cultivated land use system; the more pronounced the differentiation, the lower the resilience. Based on these findings, the primary management strategies to enhance the resilience and adaptability of the cultivated land use system include improving the production resilience of the system, increasing the enthusiasm of different types of farmers to invest in the resource elements of the cultivated land use system, promoting the transformation of ecological protection consciousness and behavior among various types of farmers, and improving the willingness for cultivated land transfer.